2013
DOI: 10.1103/physrevc.87.024303
|View full text |Cite
|
Sign up to set email alerts
|

Giant resonances in40Ca and48Ca

Abstract: We present results of fully self-consistent Hartree-Fock based random phase approximation calculations of the strength functions S(E) and centroid energies E CEN of isoscalar (T = 0) and isovector (T = 1) giant resonances of multipolarities L = 0 -3 in 40 Ca and 48 Ca, using a wide range of commonly employed 18 Skyrme type nucleonnucleon effective interactions. We determined the sensitivities of E CEN and of the isotopic differences E CEN ( 48 Ca) -E CEN ( 40 Ca) to physical quantities, such as nuclear matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 56 publications
1
39
0
Order By: Relevance
“…The observed electric monopole (E0) and isoscalar (IS) monopole strength distributions of light nuclei [1][2][3][4][5][6][7][8][9][10][11][12][13][14] show that a considerable amount of the strength fractions appears at relatively small excitation energy as sharp resonances. It was known that many of those resonances are associated with the α cluster states such as the Hoyle state of 12 C [15][16][17][18][19][20][21][22][23][24], the α + 12 C cluster states in 16 O [25,26], the α + 16 O cluster states in 20 Ne [27], and the α + α + t cluster state in 11 B [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed electric monopole (E0) and isoscalar (IS) monopole strength distributions of light nuclei [1][2][3][4][5][6][7][8][9][10][11][12][13][14] show that a considerable amount of the strength fractions appears at relatively small excitation energy as sharp resonances. It was known that many of those resonances are associated with the α cluster states such as the Hoyle state of 12 C [15][16][17][18][19][20][21][22][23][24], the α + 12 C cluster states in 16 O [25,26], the α + 16 O cluster states in 20 Ne [27], and the α + α + t cluster state in 11 B [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, one may consider the IS dipole transition, because it populates 1 − states and has an operator form that is similar to the IS monopole transition. Furthermore, its strength distributions measured for light nuclei [4][5][6]10,11,13,35,36] show the existence of the sharp resonances with enhanced strengths at relatively small excitation energies well below the giant resonance. In a recent experimental study [35], the observed low-lying resonances in 32 S are conjectured to be the α + 28 Si cluster states, because of their enhanced IS dipole transition strength from the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…However, isospin, as an approximately good quantum number in nuclei, is a useful classification of nuclear excitation modes, and reaction mechanisms often begin an oscillation in just one isospin mode. Giant Monopole resonances date experimentally to the late 1970s [4,5], and have been a topic of ongoing theoretical study [6][7][8][9], not least for their link to nuclear matter properties [10,12] In applying exact boundary conditions to the case of giant monopole resonances within the timedependent Hartree Fock framework, we use a zero-range version of the Skyrme interaction, as commonly used in exploratory work [7]. We take the parameters t 0 = −1090.0 MeV fm 3 and t 3 = 17288.0 MeV fm 6 [7] for all calculations presented.…”
Section: Giant Monopole Resonancesmentioning
confidence: 99%
“…The energy moments of the calculated strength functions were obtained using small smearing widths (0.1 MeV) to insure accuracy and they are given in Tables II-V Table IV, and 100 Mo (53±7%) are somewhat lower than the 63.85% and 61.80% obtained with the KDE0v1 interaction. The energies of the HEOR and the GQR are sensitive to the effective mass [26], and a larger effective mass would result in a lower energy for both these excitations.…”
Section: Description Of Microscopic Calculationsmentioning
confidence: 99%